Six-legged Soldiers (Wikipedia, 2022)
Six-Legged Soldiers: Using Insects as Weapons of War is a nonfiction scientific warfare book written by author and University of Wyoming professor, Jeffrey A. Lockwood. Published in 2008 by Oxford University Press, the book explores the history of bioterrorism, entomological warfare, biological warfare, and the prevention of agro-terrorism from the earliest times to modern threats. Lockwood, an entomologist, preceded this book with Ethical issues in biological control (1997) and Locust: The devastating rise and mysterious disappearance of the insect that shaped the American frontier (2004), among others.